Effects of exercise training on sleep apnoea in patients with coronary artery disease: a randomised trial. Issue 1 (13th April 2016) - Mendelson, Monique; Lyons, Owen D.; Yadollahi, Azadeh; Inami, Toru; Oh, Paul; Bradley, T. Douglas
Overnight fluid shift from the legs to the neck and lungs may contribute to the pathogenesis of obstructive sleep apnoea (OSA) and central sleep apnoea (CSA). We hypothesised that exercise training will decrease the severity of OSA and CSA in patients with coronary artery disease (CAD) by decreasing daytime leg fluid accumulation and overnight rostral fluid shift. Patients with CAD and OSA or CSA (apnoea–hypopnoea index >15 events per h) were randomised to 4 weeks of aerobic exercise training or to a control group. Polysomnography, with measurement of leg, thoracic and neck fluid volumes and upper-airway cross-sectional area (UA-XSA) before and after sleep, was performed at baseline and follow-up. 17 patients per group completed the study. Apnoea–hypopnoea index decreased significantly more in the exercise group than in the control group (31.1±12.9 to 20.5±9.4 versus 28.1±13.5 to 27.0±15.1 events per h, p=0.047), in association with a greater reduction in the overnight change in leg fluid volume (579±222 to 466±163 versus 453±164 to 434±141 mL, p=0.04) and by a significantly greater increase in the overnight change in UA-XSA in the exercise group (p=0.04). In patients with CAD and sleep apnoea, exercise training decreases sleep apnoea severity via attenuation of overnight fluid shift and an increase in UA-XSA. In patients with CAD and moderate-to-severe sleep apnoea, exercise training reduces AHI during sleep http://ow.ly/YvQzS